Radiometric Stability Assessment of the DSCOVR EPIC Visible Bands Using MODIS, VIIRS, and Invariant Targets as Independent References - Haney, Conor; Doelling, David R.; Su, Wenying; Bhatt, Rajendra; Gopalan, Arun; Scarino, Benjamin (Frontiers in Remote Sensing, 2022)
The DSCOVR mission was designed to take advantage of the first Lagrangian position (L1) to continuously observe the Earth sunlit disk. To facilitate EPIC V03 data product validation and fusion, the EPIC V03 navigation and calibration stability is assessed. The Aqua-MODIS, NPP-VIIRS, and N20-VIIRS based radiometric scaling factors are also provided. The V03 navigation error was 15.5 km, a 50% improvement over V02 and within what can be achieved by an objective image alignment algorithm. Both the navigation accuracy and precision were improved in V03 and were found to be comparable across all EPIC visible channels. The all-sky tropical ocean and deep convective cloud ray-matched MODIS- and VIIRS-referenced EPIC inter-calibration gains are within 0.4% of one-another, and are also within 0.4% of the Geogdzhayev et al. 2021 NPP-VIIRS-referenced gains. The inter-calibration study reveals that EPIC bands 5 and 6 degraded mostly within the first year of operation and becoming stable thereafter, whereas bands 7 and 10 were stable during the 6-year record. The capability of the V03 navigation allowed EPIC stability to be monitored using DCC and Libya-4 invariant targets. The EPIC V03 calibration was mostly stable within 0.3% over the 6-year record, as determined from inter-calibration and invariant target monitoring methods. Remarkably, both the DCC- and Libya-4-based methods were able to confirm the stability of the E-8 and E-9 oxygen absorptions – a stability comparable to that of the E-7 and E-10 reference bands. No significant change in the navigation accuracy or calibration stability was observed after the DSCOVR 2019 safe mode incident. The impressive stability of the DSCOVR EPIC L1B V03 channel radiances can greatly benefit the Earth remote sensing community by providing diurnally complete daytime radiative flux and environmental retrievals for future sensors located at L1.